Orexin-A/Hypocretin-1 Controls the VTA-NAc Mesolimbic Pathway via Endocannabinoid-Mediated Disinhibition of Dopaminergic Neurons in Obese Mice - Tunisi, Lea; D'Angelo, Livia; Fernández-Rilo, Alba Clara; Forte, Nicola; Piscitelli, Fabiana; Imperatore, Roberta; de Girolamo, Paolo; Di Marzo, Vincenzo; Cristino, Luigia (Frontiers in Synaptic Neuroscience, 2021)
A disinhibition of orexin-A/hypocretin-1 (OX-A) release occurs to several output areas of the lateral hypothalamus (LH) in the brain of leptin knockout obese ob/ob mice. In this study, we have investigated whether a similar increase of OX-A release occurs to the ventral tegmental area (VTA), an orexinergic LH output area with functional effects on the dopaminergic signalling at the mesolimbic circuit, and consequences on food intake and food reward. By confocal and correlative light and electron microscopy (CLEM) morphological studies coupled to molecular, biochemical and pharmacological approaches, we investigated the OX-A-mediated dopaminergic signalling at LH-VTA-nucleus accumbens (NAc) pathway in leptin knockout obese ob/ob mice compared to wild-type (wt) lean littermates. We have found increased trafficking and release of OX-A to the VTA of obese ob/ob mice in comparison to wt littermates mice. OX-A signalling promotes an over-activation of dopaminergic (DA) neurons by stimulating, via the orexin receptor-1 (OX1R), the GqPCR-mediated and phospholipase C (PLC)-diacylglycerol lipase (DAGL-α)-mediated biosynthesis and release of the endocannabinoid 2-arachidonoylglycerol (2-AG) from the VTA of ob/ob mice. By retrograde signalling to the type 1 of cannabinoid receptor (CB1R) at inhibitory inputs to DA neurons, the endocannabinoid 2-AG inhibits GABA release thus inducing a disinhibition of DA release to the VTA and NAc of ob/ob mice. This effect is prevented by OX1R or CB1R antagonists and mimicked by OX-A injection in wt littermates lean mice. Enhanced DA release to the NAc in ob/ob mice, or in OX-A-injected wt mice, is accompanied by β-arrestin2-mediated desensitization of D2 receptors in a manner prevented by an OX1R antagonist. Our data reveal that an aberrant OX-A trafficking and release occurs to the DA neurons in the VTA of ob/ob mice thus influencing the D2R response at NAc, a main target area of the mesolimbic pathway. This effect is mimicked by OX-A injection in wt lean mice thus confirming that OX-A signalling controls neuroadaptive responses to food intake by downregulation of the dopaminergic drive at D2R in the mesolimbic reward system, with putative consequences on the food reward/intake-inducing behaviours and overweight.